Changes in dynamic quadriceps angle in patients with chronic ankle instability: Cross sectional observational study - Elgendy, Mohamed; Mohamed, Esraa A; Mohamed, Aya M (International journal of health sciences, 2024)
Background: Changes in dynamic Quadriceps Angle (Q angle) had been studied in healthy subjects and individuals with other musculoskeletal disorders; however, in chronic ankle instability (CAI), it has not yet been determined. The purpose of this study was to investigate the difference in dynamic Q angle of patients with unilateral chronic ankle instability and those without chronic ankle instability. Methods: One-hundred and four participants with and without chronic ankle instability from both genders aged between 18-30 years, with a BMI range of 17.9-27.3, were enrolled into 2 equal groups; a study group and a control group, with mean values of age of the study and control groups (20.8±2.4) and (20.9±3) years respectively and of BMI (24.1±4.3) and (23.8±2.9) kg/m2 respectively. Dynamic Q angle measurement is carried out using dynamic knee valgus (DKV) through the frontal plane projection angle (FPPA) during single limb squat. Results: A statistically significant difference in FPPA angle was observed between the affected limb of the CAI group and controls (P=0.001). Conclusion: The present study suggested that unilateral CAI display an increased knee valgus, suggesting an additional proximal kinematic alteration and chronic maladaptation in the CAI population.